Exils, migrations et non-lieu identitaire dans Una Casa Vacía (1998, Raúl Osorio, TIT) - Hélène Finet (Les Cahiers ALHIM)
This article deals with the consequences of the migration process in Chilean theatre thanks to the staged presentation of Una Casa Vacía by the Taller de Investigación Teatral and Raúl Osorio in 1998, year of the Pinochet Case. Director of an independent company emblematic of theatrical counter-culture during the dictatorship years, we will show how Osorio manages to underline the issues of post-exile in the 1990’s addressing the topics of no man’s land identity meant by the impossible return to Chile.